Richard Swinburne, The Existence of God, and Principle P - Gwiazda, Jeremy (Sophia, 2009)
Swinburne relies on principle P in The Existence of God to argue that God is simple and thus likely to exist. In this paper, I argue that Swinburne does not support P. In particular, his arguments from mathematical simplicity and scientists’ preferences both fail. Given the central role P plays in Swinburne’s overall argument in The Existence of God, I conclude that Swinburne should further support P if his argument that God likely exists is to be persuasive.